The Changing Significance of the Gerebeg Maulid Tradition: An Examination of Its Socio-Economic Impact in Indonesia - Permadi, Danur Putut; Yantari, Hanif Fitri (Jurnal Sosiologi Reflektif, 2024)
The tradition of Grebeg Maulid in Yogyakarta plays a significant role within Indonesian Musim society. It is not just a cultural identity with significances of religiosity, but also a multifaceted socio-economic phenomenon. The aim of this study is to explore how the Muslim society perceives this heritage, specifically within the socio-economic context. The study employed qualitative research methodology, utilizing observation and interviews to collect data from informants who are actively engaged in the practice. The findings indicated that Grebeg Maulid serves not only as a platform for religious expression, but also as a catalyst for economic endeavors and touristic aspects. Its economic impacts are clearly identified through the numerous business transactions that take place during the event, providing a boost to the local tourism industry. However, the commercialization of this tradition has changed its meaning, with economic values overshadowing its religious significance. In a nutshell, the significance of Grebeg Maulid has undergone a significant change within Javanese Muslim culture. It has evolved beyond being solely a celebration of the Prophet Muhammad's birth and now serves as a hub for tourism and commercial endeavors in the community. Tradisi Grebeg Maulid di Yogyakarta dalam kehidupan masyarakat Muslim di Indonesia, tidak hanya sebagai simbol budaya dengan makna religius, tetapi juga sebagai fenomena sosial ekonomi yang kompleks. Penelitian ini bertujuan untuk menggali pemaknaan masyarakat Muslim terhadap tradisi ini, khususnya dalam konteks sosial ekonomi. Penelitian dilakukan dengan menggunakan metode kualitatif, adapun pengumpulan data melalui proses observasi dan wawancara dengan informan yang terlibat dalam tradisi tersebut. Hasil penelitian menunjukkan bahwa Grebeg Maulid tidak hanya menjadi sarana untuk mengekspresikan keberagamaan, tetapi juga sebagai sarana untuk aktivitas ekonomi dan pariwisata. Dimensi ekonomi dalam tradisi ini tercermin dalam bentuk transaksi ekonomi yang terjadi selama acara dan memberi dampak positif terhadap industri pariwisata setempat. Meskipun demikian, keberadaan dimensi ekonomi ini telah menggeser makna sakralitas tradisi tersebut, kebutuhan akan nilai ekonomi menjadi lebih dominan dibandingkan dengan makna religious yang melekat dalam tradisi Grebeg Maulud. Dengan kata lain, Grebeg Maulid telah mengalami transformasi makna yang signifikan bagi masyarakat Muslim Jawa, tidak lagi hanya sebagai pengingat kelahiran Nabi Muhammad, tetapi juga sebagai objek wisata dan ekonomi masyarakat.